Analysis of Student Difficulties in Completing the Final Project in Mathematics Education Study Program University of Labuhanbatu - Wafik Ajija Siregar; Indah Fitria Rahma (Budapest International Research and Critics University, 2022)
This research is included in qualitative descriptive research. The purpose of this research is to analyze what difficulties occur when students complete their final project. The research subjects were 41 respondents who were working on their final project at the Labuhanbatu University Mathematics Education Study Program. The instrument in this study used a questionnaire/questionnaire distributed via google from which was given to students online via whatsapp. Furthermore, the collected data is analyzed for description. The results of the study can show that students have difficulty in completing their final assignments. Furthermore, this research was conducted to find out how important the final project is for students and whether students are more provoking their final project. The benefit of research is to provide knowledge for researchers to be even more enthusiastic about seeking insightful knowledge, motivation and self-development and to be humble and not arrogant in the environment. The benefits for the university are consideration of the learning carried out by students and determine whether the final research project is feasible or not. The benefit for other researchers is that other researchers have more scientific insight and more ideas, abilities and skills in completing research.